2006
DOI: 10.1164/rccm.200603-360oc
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin versus Ethambutol in the First 2 Months of Treatment for Pulmonary Tuberculosis

Abstract: The addition of moxifloxacin to isoniazid, rifampin, and pyrazinamide did not affect 2-mo sputum culture status but did show increased activity at earlier time points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(190 citation statements)
references
References 27 publications
7
182
0
1
Order By: Relevance
“…Higher doses of rifampicin have been found to have better bactericidal activity (Diacon et al, 2007). Fluoroquinolones are recommended for treatment of MDRTB but new methoxyfluoroquinolones (gatifloxacin and moxifloxacin) are being evaluated for treatment shortening of drug susceptibility when substituted for ethambutol or isoniazid (Conde et al, 2009, Burman et al, 2006 New and treatment shortening studies face 2 major challenges: available 6 months regimens are effective and therefore shortening trials have to be non-inferiority trials thus requiring large samples sizes hence expensive to conduct. TB therapy is by combination, therefore, new drugs have to be effective on their own however their clinical use can only be after they are integrated into combinations.…”
Section: Treatment Shortening and New Att Drugs Studiesmentioning
confidence: 99%
“…Higher doses of rifampicin have been found to have better bactericidal activity (Diacon et al, 2007). Fluoroquinolones are recommended for treatment of MDRTB but new methoxyfluoroquinolones (gatifloxacin and moxifloxacin) are being evaluated for treatment shortening of drug susceptibility when substituted for ethambutol or isoniazid (Conde et al, 2009, Burman et al, 2006 New and treatment shortening studies face 2 major challenges: available 6 months regimens are effective and therefore shortening trials have to be non-inferiority trials thus requiring large samples sizes hence expensive to conduct. TB therapy is by combination, therefore, new drugs have to be effective on their own however their clinical use can only be after they are integrated into combinations.…”
Section: Treatment Shortening and New Att Drugs Studiesmentioning
confidence: 99%
“…The effect of replacement of EMB with standard dose of MFX or GFX (each at 400 mg) was evaluated in three separate phase II clinical trials in the intensive phase of treatment of sputum smear-positive pulmonary TB patients which yielded variable results. The first of these studies, carried out by the TB Trials Consortium, reported higher rates of sputum culture conversion at 4 and 6 weeks of therapy but not at week 8 in MFX-containing regimen [42]. Another study conducted in Rio de Janeiro, Brazil, also reported higher rates of sputum culture conversion beginning at 2 weeks and persisting till week 8 of therapy in MFXcontaining regimen [43].…”
Section: Fluoroquinolones As Anti-tb Drugsmentioning
confidence: 99%
“…The results of the four phase II trials involving MFX and GFX have shown that replacement of either MFX or GFX with EMB or replacement of MFX with INH is at least as efficacious as the standard intensive phase of therapy and may even contribute towards more rapid clearing of the infected lungs by rapidly dividing tubercle bacilli [42][43][44][45]. Both mFQs are now in two separate phase III clinical trials for the treatment of adult patients newly diagnosed with drug sensitive, pulmonary TB for investigation of whether treatment duration can be effectively shortened to 4 months by substitution of GFX for EMB or MFX for either EMB or INH [49,50].…”
Section: Fluoroquinolones As Anti-tb Drugsmentioning
confidence: 99%
“…Encouragingly, a more potent extended EBA, that is, from days 2 to 7, was observed with the FQs than for INH [47]. A recent Phase II trial to investigate whether MXF could replace EMB in INH plus PZA plus RIF plus EMB combinations revealed that, although the MXF regimes showed more frequent sputum conversion at 4 weeks, the success of the treatments provided identical outcomes after 2 months [49]. The 2-month timepoint coincides with the end of the intensive phase of treatment with common regimens, and culture conversion rates at this stage are a well-accepted surrogate marker for the sterilizing activity of anti-tuberculosis drugs.…”
Section: Quinolonesmentioning
confidence: 99%